Produção de enzimas celulolíticas de Trichoderma reesei por fermentação em estado sólido e sua aplicação na sacarificação de resíduos agroindustriais lignocelulósicos - Gasparotto, Juliana Machado (2014)
Sugarcane bagasse is an abundant lignocellulosic residue in traditional regions of sugar and ethanol production in Brazil. It is not only a potential substrate for second generation ethanol production but also have structural features to be classified as good inducer for cellulases production by microorganisms. However, the high cost of cellulases industrial production is the major bottleneck in the hydrolysis of this raw material for subsequent fermentation, which makes unfeasible in large scale the ethanol production using this process. In this context, the development of more efficient and less expensive fermentation processes for industrial cellulases production, as well as better alternatives of enzymatic hydrolysis of lignocellulosic material is crucial to achieve economic feasibility in this process. For this purpose, this work aims to develop a cellulase production process using Trichoderma reesei, as well as assessing the use of produced enzymatic extract in sugarcane bagasse hydrolysis, in order to evaluate the ultrasound effects in the hydrolysis process. The optimized process of cellulases production consisted in five days of grow in pre-inoculum Petri dishes, followed by two days of grow in optimized liquid medium and four days of solid state fermentation, using sugarcane bagasse supplemented with 1% of soybean bran and 15% (v/w) of corn steep liquor as substrate, moisture of 65%, 28±1°C and 0.5 mL of inoculum per gram of substrate. This experimental condition in bench scale (5 g) resulted in a production of 1.4 FPU/g of cellulases, and the production was approximately three-fold high in a fixed-bed bioreactor with forced aeration for 70 g of substrate capacity. For ultrasound assisted enzymatic hydrolysis using an ultrasound bath, the condition that achieved higher efficiencies were 43.4±2°C and 18.5% (v/v) of enzyme concentration, resulting in a maximal hydrolysis efficiency of 229 grams of reducing sugar per kilogram of used substrate, achieving an average increase of 12% in efficiency in those experiments where the hydrolysis was assisted by ultrasound compared with those without sonication. Regarding the saccharification using the ultrasonic probe, results using the indirect sonication during process were, on average, 158% higher than those using the direct sonication. Thus, it can be concluded that indirect sonication is more suitable to be used as an auxiliary in the hydrolysis, since the direct sonication can cause denaturation of the enzyme, reducing the process efficiency.